Comparative Study Between Virtual Laboratory PhET Colorado Versus Applets in Photoelectric Effect - Az-zahra, Puput Lismanda; Rohim, Fahmi; Amarulloh, Reza Ruhbani; Nanto, Dwi; Herpi, Aini Nadhokhotani (Kasuari: Physics Education Journal (KPEJ), 2024)
Our work describes the differences and similarities in several aspects between two virtual laboratory (lab) media, namely Physics Education Technology (PhET) Colorado and Applets the King’s Centre forVvisualization (KCVS). The aspects compared include website appearance, ease of access and use, strengths and weaknesses of each virtual lab, and support for relevant concepts. Virtual lab such PhET Colorado and Applets provide a viable alternative, offering a safe and immersive environment for students to engage with scientific phenomena. The research used a qualitative descriptive approach with a comparative method. The researcher will compare the two virtual lab based on the aforementioned aspects. We find that the PhET Colorado website excels in visualization and data interpretation, meanwhile the Applet website excels in the availability of literature related to the photoelectric effect material.